Solvation properties of protic ionic liquids 2-methoxyethylammonium nitrate, propylammonium hydrogen sulfate, and butylammonium hydrogen sulfate. (July 2022) - Sedov, Igor A.; Magsumov, Timur I.
Highlights: Limiting activity coefficients of hydrocarbons and alcohols were measured. The solubility of hydrocarbons in studied ILs is lower than in alkylammonium nitrates. CH3 O group destabilizes apolar domains in IL and disfavors hydrocarbon solubility. Hydrogen sulfate anion forms strong H-bonds and hinders hydrocarbon solubility. Abstract: Solvation properties of protic ionic liquids (PILs) are virtually unexplored. We measured the limiting activity coefficients of several hydrocarbons and aliphatic alcohols in 2-methoxyethylammonium nitrate (2MEAN), propylammonium hydrogen sulfate (PAHS), and butylammonium hydrogen sulfate (BAHS) at 298 K. Comparison with the previously obtained results for other substituted ammonium PILs reveals the sensitivity of solvation properties to the changes in the structure of both cation and anion which also affect the nanostructure of the bulk phase. It was shown that hydrocarbons are less soluble in 2MEAN than in alkylammonium nitrates due to destabilizing effect of the methoxy group on apolar domains in the liquid structure preferentially solvating hydrocarbon molecules. The solubility of hydrocarbons is also lower in hydrogen sulfate ILs than in nitrate ILs with the same alkylammonium cation. This can be explained by the presence of the acidic hydrogen in anion which strengthens the hydrogen bonds network and the solvophobic effects in the liquid.